Exposure to Amoxicillin in Early Life Is Associated With Changes in Gut Microbiota and Reduction in Blood Pressure: Findings From a Study on Rat Dams and Offspring. Issue 2 (21st January 2020) - Galla, Sarah; Chakraborty, Saroj; Cheng, Xi; Yeo, Ji‐Youn; Mell, Blair; Chiu, Nathaline; Wenceslau, Camilla F.; Vijay‐Kumar, Matam; Joe, Bina
Abstract : Background: Pediatric hypertension is recognized as an emerging global health concern. Although new guidelines are developed for facilitating clinical management, the reasons for the prevalence of hypertension in children remain unknown. Genetics and environmental factors do not fully account for the growing incidence of pediatric hypertension. Because stable bacterial flora in early life are linked with health outcomes later in life, we hypothesized that reshaping of gut microbiota in early life affects blood pressure (BP) of pediatric subjects. Methods and Results: To test this hypothesis, we administered amoxicillin, the most commonly prescribed pediatric antibiotic, to alter gut microbiota of young, genetically hypertensive rats (study 1) and dams during gestation and lactation (study 2) and recorded their BP. Reshaping of microbiota with reductions in Firmicutes/Bacteriodetes ratio were observed. Amoxicillin treated rats had lower BP compared with untreated rats. In young rats treated with amoxicillin, the lowering effect on BP persisted even after antibiotics were discontinued. Similarly, offspring from dams treated with amoxicillin showed lower systolic BP compared with control rats. Remarkably, in all cases, a decrease in BP was associated with lowering of Veillonellaceae, which are succinate‐producing bacteria. Elevated plasma succinate is reported in hypertension. Accordingly, serum succinate was measured and found lower in animals treated with amoxicillin. Conclusions: Our results demonstrate a direct correlation between succinate‐producing gut microbiota and early development of hypertension and indicate that reshaping gut microbiota, especially by depleting succinate‐producing microbiota early in life, may have long‐term benefits for hypertension‐prone individuals.